Frontline Employees’ Motivation towards Customers’ Value Outcomes: A Context of Non-Fuel Retailing - Abid, Muhammad Farrukh; Nawaz, Muhammad; Siddique, Junaid; Johl, Satirenjit Kaur; Nadeem, Muhammad Aamir; Mazhar, Muhammad (Jurnal The Messenger, 2022)
Introduction: The present study aimed to explore the frontline employees in-shop motivation to influence the customers in-shop emotions. The study further proposed the conceptual foundations of the dynamic nature of value outcomes in non-fuel retail stations, where each customer perceives the interaction with frontline employee differently. Therefore, the value outcomes based on the customers’ in-shop emotions were dynamic.Methods: The study had used the content analysis to seek the outcome where the data was collected using open-ended interviews from frontline employees and customers of non-fuel retail outlets in Malaysia. The sample size was 12 using the snowball technique, including 6 frontline employees in phase 1 and 6 customers in phase 2 who had visited the same non-fuel retail outlets used in phase 1 for data collection.Findings: The results showed interesting findings where it was observed that customers get positive and negative influence emotionally through individual interaction with frontline employees. Furthermore, the positive/negative emotions helped the customers to create or destroy the value individually. These service encounters are subjective and vary from customer-customer affecting their emotions differently are therefore cannot be generalized on the large set of audience.Originality: Through the lens of S-D logic paradigm, the present study has conceptualized the dynamic nature of emotions which can lead towards value creation/value destruction or value destruction/value creation in different situations and contexts based on the individual service encounters of customers-frontline employees within non-fuel retail shops.